Eroticism, Spirituality, and Resistance in Black Women's Writings - Weir-Soley, Donna (Book collections on Project MUSE., 2009)
The author builds on previous scholars' work identifying the ways that black women's narratives often contain a form of spirituality rooted in African cosmology, which consistently grounds their characters' self-empowerment and quest for autonomy. What she adds to the discussion is an emphasis on the importance of sexuality in the development of black female subjectivity.